A biobased degradable high-efficiency antibacterial medical dressing and a preparation method thereof
Patent Information
- Application Number
- CN202610975912.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-02
AI Technical Summary
例如,公开号为CN104857553A的中国专利文献公开了的医用敷料制备方法仍存诸多缺陷:所用基材为不可降解石油基聚合物,溶剂易残留并引发皮肤刺激,纳米银易氧化失效、硼砂存在潜在毒性;制得的纤维膜湿态强度低、吸液能力不足,无控释设计致使抗菌功效难以持续
本发明通过多层的层状结构与天然材料组合,采用超声焊接的方式进行复合,接触层和功能层包含多种天然抑菌抗炎药物,从而实现了多重优势:
Smart Images

Figure CN122461530B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical materials technology, specifically to a bio-based, biodegradable, highly effective antibacterial medical dressing and its preparation method. Background Technology
[0002] Medical dressings are essential medical products used to cover and protect wounds, absorb secretions, and promote wound healing. They are suitable for clinical scenarios such as postoperative incision care, management of exudate from chronic ulcers, and pressure ulcer care for long-term bedridden patients. Traditional medical dressings, such as gauze, have a single function, only providing physical coverage and lacking active functions such as antibacterial and healing-promoting properties.
[0003] In recent years, with the development of materials science, various functional dressings have emerged. For example, the medical dressing preparation method disclosed in Chinese patent document CN104857553A still has many defects: the substrate used is a non-degradable petroleum-based polymer, the solvent is easy to remain and cause skin irritation, the nano-silver is easy to oxidize and fail, and borax has potential toxicity; the resulting fiber membrane has low wet strength and insufficient liquid absorption capacity, and the lack of controlled release design makes it difficult to maintain antibacterial efficacy.
[0004] Chinese patent document CN110433320A discloses a method for preparing medical dressings using a combination of sub-pluripotent stem cell secretin, PLGA sustained-release microspheres, and hyaluronic acid hydrogel, with an electrospun membrane as a carrier. However, the preparation method still has many defects: the degradation rate of PLGA microspheres does not match the wound healing cycle; acidic degradation products are prone to causing inflammation; the hyaluronic acid hydrogel has poor wet strength and unstable structure; the extraction and purification process of stem cell secretin is unclear, and its activity is easily inactivated; the encapsulation rate and drug loading of microspheres lack quality control; and the active factors are unevenly dispersed; secretin has the risk of allergic protein sensitization, and there is a lack of immunogenicity and long-term toxicity assessment data; it lacks antibacterial design and is not suitable for infected wounds.
[0005] Chinese patent document CN104784743A discloses a method for preparing an aromatic antibacterial chitosan-based wound dressing. This method involves mixing tea tree oil, menthol, and mugwort oil in a specific ratio to obtain a natural aromatic antibacterial agent, encapsulating it in liposomes to obtain aromatic antibacterial liposomes, dispersing them in a chitosan-sodium alginate-gelatin solution, and then freeze-drying them according to a specific procedure to obtain the aromatic antibacterial chitosan-based wound dressing. However, this method still has many drawbacks: natural essential oils are volatile, liposomes are prone to aggregation, resulting in poor long-lasting antibacterial properties; the freeze-dried porous structure has low wet strength, easily adhering to the wound surface after liquid absorption, causing secondary damage; menthol carries the risk of sensitizing or irritating burn wounds, and the freeze-drying process is costly and difficult to scale up.
[0006] Therefore, developing a medical dressing that combines multiple functions such as high-efficiency antibacterial properties, super absorption, biodegradability, and safety and non-toxicity has become an urgent technical problem to be solved in this field. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides a bio-based, biodegradable, highly effective antibacterial medical dressing. This medical dressing is highly effective in inhibiting bacteria and reducing inflammation, and is suitable for antibacterial, anti-inflammatory, and wound-healing care for various wounds. It is also biodegradable and easy to dispose of after use.
[0008] A bio-based, biodegradable, highly effective antibacterial medical dressing comprises a contact layer, a functional layer, a support layer, and a backing layer integrated into one piece. The contact layer is a nanofiber membrane loaded with natural plant essential oils, and the functional layer is a composite layer composed of microspheres loaded with anti-inflammatory drugs, modified starch, and oxidized regenerated cellulose.
[0009] In this invention, the contact layer uses fully biodegradable materials and natural antibacterial and anti-inflammatory components, which are gentle and non-irritating to the wound. At the same time, the nanofiber membrane made by electrospinning provides an ideal scaffold for cell growth and accelerates wound healing. The functional layer uses a combination of oxidized regenerated cellulose and modified starch to achieve rapid absorption and active hemostasis, while the microspheres loaded with anti-inflammatory drugs achieve long-term, targeted release of the anti-inflammatory drugs. The support layer ensures structural stability, while the backing layer achieves a perfect balance between leak prevention and breathability.
[0010] Preferably, the natural plant essential oil in the contact layer is one or more of the following: thyme essential oil, lavender essential oil, tea tree essential oil, Roman chamomile essential oil, eucalyptol-type rosemary essential oil, geranium essential oil, myrrh essential oil, mugwort essential oil, peppermint essential oil, and honeysuckle essential oil.
[0011] Plant essential oils, as natural mixtures, contain compounds such as terpenes, monoterpenes, alcohols, or aldehydes, such as terpinene-4-ol in tea tree oil and geraniol in geranium oil. These compounds can exhibit highly effective antibacterial properties through interactions with bacterial cell membranes or metabolic pathways.
[0012] Preferably, the nanofiber membrane is composed of chitosan and polycaprolactone, wherein the mass ratio of chitosan to polycaprolactone is 0.8~1.5:6~10.
[0013] In this invention, chitosan loaded with releasable chitosan oligosaccharides endows the nanofiber membrane with significant antibacterial and bactericidal capabilities; polycaprolactone provides high hydrophobicity and excellent antibacterial adhesion properties. Together, they achieve a dual antibacterial function of "anti-adhesion + bactericidal". Simultaneously, the nanofiber membrane possesses good biocompatibility, mechanical properties, thermal stability, water absorption, and permeability, and can also guide epithelial cell crawling and repair. Therefore, the nanofiber layer can maintain a suitable wound healing microenvironment, meeting the requirements for medical dressings.
[0014] More preferably, the natural plant essential oil is one of the following: a blend of thyme essential oil and lavender essential oil, tea tree essential oil, a blend of tea tree essential oil and Roman chamomile essential oil, a blend of eucalyptol-type rosemary essential oil and geranium essential oil, or a blend of myrrh essential oil, honeysuckle essential oil, and mugwort essential oil.
[0015] More preferably, the mass ratio of the natural plant essential oil to the nanofiber membrane is 1:8~25.
[0016] Preferably, the anti-inflammatory drugs in the microspheres loaded with anti-inflammatory drugs are one or more of curcumin, berberine, baicalin, aloe-emodin, chlorogenic acid, and gallic acid, and the microsphere carriers are one or more of sodium alginate, potassium alginate, sodium carboxymethyl cellulose, chitosan, pectin, and sodium hyaluronate. These natural polymer compounds are all water-soluble and easily degraded.
[0017] More preferably, the mass ratio of the anti-inflammatory drug to the microsphere carrier is 8~12:90~110.
[0018] More preferably, the water content of the microspheres loaded with anti-inflammatory drugs is 5-10 wt%.
[0019] Preferably, the modified starch is modified by grafting with a polymer compound, wherein the polymer compound is one or more of chitosan, carboxymethyl chitosan, quaternized chitosan, sodium alginate, sodium carboxymethyl cellulose, sodium hyaluronate, pectin, and polyvinyl alcohol.
[0020] Modified starch is based on the abundant hydroxyl, amino, and carboxyl groups on the starch molecular chain. Through chemical grafting reactions (such as condensation reactions, Schiff base reactions, or free radical copolymerization), polymeric compounds are covalently linked to the starch backbone. After grafting these water-soluble polymeric compounds, the water solubility and dispersibility of modified starch are usually significantly improved, while the starch backbone and the grafted natural polysaccharides such as chitosan, sodium alginate, and sodium hyaluronate still maintain biodegradability.
[0021] In addition, modified starch is endowed with the unique functions of the grafted components, such as the long-lasting antibacterial properties of quaternized chitosan, the ionic cross-linking and gelling properties of sodium alginate, the film-forming toughness enhanced by polyvinyl alcohol, and the mucosal adhesion and hemostatic effects provided by cationic chitosan, which can be used in antibacterial dressings.
[0022] More preferably, the polymer compound is chitosan, and the moisture content of the chitosan-grafted modified starch after drying is 8-12 wt%.
[0023] In this invention, because chitosan contains a large number of amino groups, it can be grafted with starch. After grafting, starch has a strong adsorption force on negatively charged mucous membranes and cell surfaces, and endows it with excellent antibacterial properties.
[0024] Preferably, in the functional layer, the mass ratio of the microspheres loaded with anti-inflammatory drugs, modified starch, and oxidized regenerated cellulose is 2~3:2~4:4~6.
[0025] Preferably, the support layer is a composite meltblown nonwoven fabric of polylactic acid (PLA) and polycaprolactone (PCL), wherein the mass ratio of PLA to PCL is 3-4:1-2; and the areal density of the composite meltblown nonwoven fabric is 18-22 g / m². 2 .
[0026] Preferably, the backing layer is a polybutylene succinate (PBS) microporous membrane, wherein the pore size of the microporous membrane is 0.1~1 μm, achieving air permeability without water permeability, preventing leakage, and preventing external bacterial invasion.
[0027] Preferably, in the bio-based biodegradable high-efficiency antibacterial medical dressing, the interlayer peel strength of each layer is ≥1.5 N / 15 mm.
[0028] This invention also provides a method for preparing the above-mentioned bio-based biodegradable high-efficiency antibacterial medical dressing, comprising the following steps: (1) Preparation of contact layer: Chitosan and polycaprolactone are added to a mixed solvent of acetic acid aqueous solution and ethanol, stirred in a water bath until dissolved, and then natural plant essential oil is added. After ultrasonic degassing, a spinning solution is obtained. The spinning solution is electrospun and then vacuum dried to obtain a contact layer of nanofiber membrane loaded with natural plant essential oil. (2) Preparation of functional layer: anti-inflammatory drugs and microsphere carriers are mixed and cross-linked to obtain microspheres loaded with anti-inflammatory drugs; polymer compounds and starch are subjected to cross-linking reaction to obtain modified starch grafted with polymer compounds; microspheres loaded with anti-inflammatory drugs, modified starch and oxidized regenerated cellulose are mixed, water is added to make paste, molded, vacuum dried and sterilized to obtain functional layer; (3) Preparation of support layer: Polylactic acid and polycaprolactone are mixed evenly by melt extrusion, and then drawn into fiber filaments by high temperature airflow. After hot air gradient shaping, sterilization and analysis, the support layer of polylactic acid and polycaprolactone composite meltblown nonwoven fabric is obtained. (4) Preparation of backing layer: Polybutylene succinate is blown into a film and melt extruded to obtain a base film. The base film is biaxially stretched to form a microporous membrane with uniform pore size. After shaping and sterilization, the backing layer of polybutylene succinate microporous membrane is obtained. (5) The above-mentioned contact layer, functional layer, support layer and backing layer are activated by plasma and then composited by ultrasonic welding to obtain a bio-based biodegradable high-efficiency antibacterial medical dressing.
[0029] In this invention, the contact layer, functional layer, support layer, and backing layer are ultrasonically welded together to form a single unit, resulting in an interlayer peel strength of ≥15 N / 15 mm for each layer of the medical dressing, and a strong bond between the layers.
[0030] Preferably, in step (1), the temperature of the water bath is 40~50 ℃, the stirring speed is 300~500 r / min, and the stirring time is 1~1.5 h.
[0031] Preferably, in step (1), the ultrasonic debubbling process uses an ultrasonic power of 200-300 W, a frequency of 20-25 kHz, and an ultrasonic duration of 10-15 min.
[0032] Preferably, in step (1), the parameters of the electrospinning are as follows: voltage is 17~19 kV, receiving distance is 14~16 cm, feed speed is 0.4~0.6 mL / h, temperature is 18~25 ℃, and relative humidity of the environment is 40%~50%.
[0033] Preferably, in step (1), the vacuum drying temperature is 28~32 ℃, the vacuum degree is -0.07~-0.09MPa, and the drying time is 4~6 h.
[0034] Preferably, in step (2), the preparation method of the microspheres loaded with anti-inflammatory drugs is as follows: the anti-inflammatory drug is pre-dissolved in anhydrous ethanol or dimethyl sulfoxide, and then added to the aqueous solution of the microsphere carrier. The solution is dissolved by ultrasonication to obtain a mixed solution of anti-inflammatory drug and microsphere carrier. The mixed solution is added dropwise to calcium chloride solution by peristaltic pump, and microspheres are formed after stirring, solidification and cross-linking.
[0035] More preferably, the conditions for ultrasonic dissolution are: ultrasonic power of 200~300 W and ultrasonic time of 15~20 min.
[0036] More preferably, the dripping rate of the mixed solution is 1~2 mL / min.
[0037] More preferably, the curing and crosslinking time is 25-35 min.
[0038] Preferably, in step (2), the initiator in the crosslinking reaction is sodium persulfate, and the initiator accounts for 1.0 to 1.5 wt% of the total mass of the polymer and starch; the crosslinking agent is N,N'-methylenebisacrylamide (MBA), and the crosslinking agent accounts for 0.15 to 0.2 wt% of the total mass of the polymer and starch.
[0039] Preferably, in step (2), the pressure of the molding process is 0.5~1.0 MPa.
[0040] Preferably, in step (2), the vacuum drying temperature is 30~40 ℃, the vacuum degree is -0.06~-0.09MPa, the time is 4~8 h, and the moisture content of the functional layer after drying is 6~9 wt%.
[0041] Preferably, in step (3), the temperature of the melt extrusion is set sequentially from the hopper to the spinneret to 170~180℃, 180~190℃, and 190~195℃, and the screw speed is 30~50 r / min.
[0042] Preferably, in step (3), the hot air gradient shaping is specifically: first, keep warm at 60~70 ℃ for 4~6 min, and then raise the temperature to 80~90 ℃ and keep warm for 9~11 min.
[0043] Preferably, in step (3), the sterilization is performed using ethylene oxide, wherein the sterilization concentration of ethylene oxide is 450~600 mg / L, and the desorption time is 7~10 days.
[0044] Preferably, in step (4), the biaxial stretching step specifically involves: after preheating the base film, longitudinal stretching is first performed at a stretching temperature of 80~90 ℃ and a stretching rate of 50~100 mm / min, followed by transverse stretching at a stretching temperature of 85~95 ℃ and a stretching rate of 80~120 mm / min, with both longitudinal and transverse stretching ratios being 2.5~3.5 times; during the stretching process, the longitudinal tension is maintained at 50~100N and the transverse tension at 80~150N.
[0045] Preferably, in step (5), the plasma activation power is 150~200 W and the time is 3~5 min.
[0046] Preferably, in step (5), the ultrasonic welding parameters are: ultrasonic frequency 20~40 kHz, welding pressure 0.1~0.3 MPa, welding time 0.5~2 s, and holding time 1~3 s.
[0047] The present invention also provides the above-mentioned bio-based biodegradable high-efficiency antibacterial medical dressing, which is suitable for the care and repair of various superficial wounds, abrasions, cuts, postoperative wounds and chronic wounds.
[0048] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention combines a multi-layered structure with natural materials and employs ultrasonic welding for composite bonding. The contact layer and functional layer contain various natural antibacterial and anti-inflammatory drugs, thus achieving multiple advantages: 1. This invention utilizes entirely bio-based biodegradable materials, exhibiting low cytotoxicity, safe use, and convenient post-use disposal. For example, the nanofiber membrane in the contact layer is electrospun from chitosan and polycaprolactone; the microspheres in the functional layer and the starch-modified polymers are water-soluble natural polymers, all of which are biodegradable. The resulting medical dressing exhibits no significant skin irritation or cytotoxicity, with a mass loss rate ≥5% in simulated body fluids.
[0049] 2. The contact layer of the present invention contains natural plant essential oils, and the functional layer contains anti-inflammatory drugs. The gentle natural plant essential oils inhibit bacteria and reduce inflammation on the wound, while the anti-inflammatory drugs loaded on the microspheres of the functional layer achieve long-lasting and targeted release. The two work together to achieve an antibacterial rate of up to 95% against Staphylococcus aureus and prolong the anti-inflammatory time, giving the medical dressing excellent antibacterial and anti-inflammatory effects.
[0050] 3. This invention integrates the contact layer, functional layer, support layer, and backing layer into one unit through ultrasonic welding, resulting in an interlayer peel strength of ≥15 N / 15 mm for each layer of the medical dressing. The layers are firmly bonded together, and the four structural layers that can synergistically leverage their respective advantages achieve functions such as efficient absorption, precise drug release, wound healing guidance, and biodegradation, resulting in synergistic effects and safe use. Attached Figure Description
[0051] Figure 1 This is a schematic diagram of the structure of a bio-based, biodegradable, highly effective antibacterial medical dressing.
[0052] Figure 2 The graph shows the test data of the beneficial effects of the bio-based biodegradable high-efficiency antibacterial medical dressing prepared in Example 1.
[0053] Figure 3 The images are of the bio-based biodegradable high-efficiency antibacterial medical dressing prepared in Example 1, wherein A is taken from the contact layer direction and B is taken from the backing layer direction. Detailed Implementation
[0054] The present invention will be further described in detail below with reference to the embodiments, but the implementation of the present invention is not limited to the following embodiments.
[0055] All raw materials used in this invention are commercially available.
[0056] Example 1 (1) Preparation of contact layer S11. Preparation of spinning solution: Weigh 1.1 g of chitosan and 8 g of polycaprolactone (PCL), and add them to a 1 wt% acetic acid aqueous solution-ethanol mixed solvent with a volume ratio of 3:2, wherein there are 120 mL of 1 wt% acetic acid aqueous solution and 80 mL of ethanol; under a water bath at 45 ℃, stir magnetically at 400 r / min for 1.2 h until the polymer is completely dissolved; then add 0.8 g of thyme and lavender mixed essential oil (accounting for 0.41 wt% of the total mass fraction of the spinning solution); use ultrasonic dispersion at 250 W and 20 kHz for 15 min; then let stand at 25±2 ℃ for 30 min to degas, with nitrogen gas purging throughout the process to obtain a uniform and stable spinning solution; S12. Electrospinning and Drying: Inject the spinning solution into the storage device of the electrospinning equipment and set the process parameters: voltage 18 kV, receiving distance 15 cm, feed speed 0.5 mL / h; spinning ambient temperature 21 ℃, relative humidity 45%; start electrospinning, collect the nanofiber membrane on the receiving device, and control the thickness of the fiber membrane to 0.15±0.05 mm; stop spinning after reaching the preset thickness, remove the nanofiber membrane, place the nanofiber membrane in a vacuum drying oven, and dry it at 30 ℃ and vacuum degree -0.08 MPa for 5 h to fully remove residual solvent, and obtain a nanofiber membrane with natural plant essential oil, i.e., the contact layer.
[0057] (2) Preparation of functional layer S21. Preparation of microspheres loaded with anti-inflammatory drugs: Weigh 10 g of sodium alginate, 1.0 g of curcumin, and 100 mL of deionized water by mass percentage. Pre-dissolve the curcumin in a small amount of anhydrous ethanol, then add it to the sodium alginate aqueous solution. Place the solution in an ultrasonic dispersion device under light-protected conditions. The ultrasonic power is 250 W, and the ultrasonic time is 17 min, until the system is homogeneous and free of obvious particles, thus obtaining a sodium alginate-curcumin mixture.
[0058] Under conditions of complete darkness, the above mixture was added dropwise to a 2 wt% calcium chloride solution at a flow rate of 1.5 mL / min using a peristaltic pump. The volume of the calcium chloride solution was 1000 mL. The stirring speed was 250 r / min, and the mixture was continuously stirred and solidified for 30 min to complete the ion cross-linking into spheres.
[0059] The entire process was carried out under light-protected conditions. Microspheres in the system were collected by filtration and washed three times with deionized water to remove residual calcium chloride. Finally, the microspheres were placed in a vacuum drying oven at 35 °C and a vacuum of -0.08 MPa for 5 h, resulting in a moisture content of 8%. Alginate microspheres loaded with curcumin were obtained.
[0060] S22. Preparation of modified starch grafted with polymeric compounds: Weigh 50 g of corn starch and add it to 500 mL of deionized water. Heat the system to 80 °C and gelatinize for 40 min to obtain a starch paste. Weigh 10 g of chitosan and dissolve it in 500 mL of 1 wt% acetic acid solution. Stir in a 35 °C water bath until the chitosan is completely dissolved. Add the dissolved chitosan to the starch paste and adjust the system temperature to 60 °C. React at this temperature for 2 h.
[0061] Add 0.8 g of ammonium persulfate and 0.1 g of N,N'-methylenebisacrylamide to the reaction system and continue the reaction at 60°C for 3 h.
[0062] After the reaction was completed, the product was repeatedly filtered and washed three times with deionized water, and finally rinsed twice with gradient concentrations of ethanol. The first rinse was with 30 vol% (volume fraction) ethanol solution, and the second rinse was with 50 vol% (volume fraction) ethanol solution to remove residual acetic acid, unreacted ammonium persulfate and MBA from the system. Vacuum drying was carried out at 55 ℃ and a vacuum degree of -0.08 MPa for 6 h, with a moisture content of 10%. After pulverization, the product was passed through a 100-mesh sieve to obtain chitosan grafted modified starch.
[0063] S23. Preparation of functional layer: Weigh 4 g of curcumin-loaded alginate microspheres, 6 g of chitosan-grafted modified starch, and 10 g of oxidized regenerated cellulose (ORC) according to a mass ratio of 2:3:5. Mix the three materials and stir evenly.
[0064] Add 17 wt% deionized water to the mixture, stir until the material is a spreadable paste, use medical grade silicone oil as the release agent, pour it into a mold, spread it into a sheet with a thickness of 2 mm, and apply a pressure of 0.8 MPa.
[0065] The mold and the sheet were placed in a vacuum drying equipment and dried at 30 ℃ for 1 h, then the temperature was raised to 50 ℃ for 1 h. The vacuum degree was -0.08 MPa and the moisture content was 9%. After the product was solidified and formed, it was taken out and sterilized with 60 Co γ-rays to obtain the functional layer.
[0066] (3) Preparation of the support layer PLA (REVODE 701) and PCL (CAPA 6500) granules were placed separately in a vacuum drying oven and dried at 50°C for 3 hours, followed by drying at 60°C for 5 hours. 7 kg of dried PLA and 3 kg of dried PCL granules were weighed at a mass ratio of 7:3, and 2.5 wt% of the medical-grade compatibilizer DSM-Firmenich BioSpan was added. ® Add S (block polyether polyurethane) to a high-speed mixer and stir at 1000 r / min for 15 min to ensure uniform mixing of the materials.
[0067] The mixed materials are fed into the hopper of the meltblown extruder; the temperature of the extruder section is set sequentially from the hopper to the spinneret at 175 ℃, 185 ℃, and 190 ℃, and the screw speed is 40 r / min, so that the raw materials are melted and mixed into a uniform melt.
[0068] The molten polymer is precisely delivered by a metering pump, according to the target basis weight of 20 g / m³. 2 Adjust the metering pump speed to ensure stable and quantitative delivery of the melt to the spinneret. After the melt is extruded from the micropores of the spinneret, a high-temperature and high-pressure airflow at 200 ℃ and 0.4 MPa is introduced from both sides to stretch the melt stream, rapidly drawing it into micron-sized fibers.
[0069] Driven by the stretching airflow, the ultrafine fibers are blown onto the forming curtain and deposited evenly; by adjusting the speed of the metering pump and the running speed of the forming curtain in a coordinated manner, the basis weight of the fiber web is precisely controlled to reach 20 g / m². 2 The fiber web is fed into a continuous hot air setting oven and set in a gradient: 65 ℃ for 5 min, then heated to 85 ℃ for 10 min, and finally cooled to below 40 ℃ before being discharged, thus improving the structural stability between fibers.
[0070] The shaped fiber web was sterilized with ethylene oxide at a concentration of 500 mg / L, a temperature of 45 ℃, a pressure of 0.15 MPa, and a time of 2.5 h. After sterilization, it was placed in a well-ventilated and clean environment at a temperature of 40 ℃ and a humidity of 50% for 7 days to remove residual ethylene oxide, yielding a composite meltblown nonwoven fabric of polylactic acid and polycaprolactone, i.e., the support layer.
[0071] (4) Preparation of backing layer Take PBS raw material of Lanshan Tunhe brand TH-PBS-600, place it in a vacuum drying oven with a vacuum degree of -0.08 MPa, dry at 70 ℃ for 3 h, and the moisture content of the dried product is <0.2%.
[0072] The dried PBS particles were added to the hopper of the blown film extruder. The extrusion temperature was controlled in stages: 125 ℃ at the front of the barrel, 140 ℃ in the middle, and 145 ℃ at the die head, with a temperature fluctuation range of ≤±3 ℃. After melt extrusion, the film was blown into bubbles through a ring die. The blow-up ratio was first pre-blown at 1.5:1, and then stretched to 2.5:1 to avoid bubble rupture. The bubbles were then rapidly cooled and set at 20 ℃ using a cooling air ring with an air velocity of 5 m / s, and finally wound up to obtain the PBS base film.
[0073] With an ambient relative humidity of 35%, the PBS base film was placed in a stretching machine and preheated at 65 ℃ for 7 s. Then, longitudinal stretching was performed, with the stretching temperature controlled at 85 ℃ and the stretching rate at 75 mm / min. Transverse stretching was then performed, with the stretching temperature controlled at 85 ℃ and the stretching rate at 90 mm / min. The stretching ratio for both longitudinal and transverse stretching was 3 times. During the stretching process, the longitudinal tension was maintained at 80 N and the transverse tension at 110 N to ensure that the base film formed a microporous structure with uniform pore size of 0.1~1 μm.
[0074] The stretched microporous membrane was heat-set at 80 ℃ for 20 s to eliminate internal stress and prevent membrane shrinkage and deformation. Plasma treatment was then performed at 250 W power, 25 L / min air medium flow rate, 15 Pa chamber pressure for 8 min to improve the composite adhesion between the microporous membrane and the functional layer and prevent delamination during use.
[0075] The shaped microporous membrane was sterilized with ethylene oxide at a concentration of 500 mg / L, a temperature of 45℃, a pressure of 0.15 MPa, and a time of 3 h. After sterilization, it was placed in a well-ventilated and clean environment at a temperature of 40℃ and a humidity of 50% for 7 days to remove residual ethylene oxide. Finally, it was rolled up and cut to obtain a PBS microporous membrane for the backing layer.
[0076] (5) Preparation of bio-based biodegradable high-efficiency antibacterial medical dressings Before welding, the substrate is cleaned using plasma cleaning at a power of 150 W for 5 minutes to clean the substrate surface and improve the interlayer fusion bonding force.
[0077] The contact layer, functional layer, support layer, and backing layer are taken in sequence and laid on the worktable mold of the ultrasonic welding equipment from top to bottom. The positioning vacuum adsorption positioning device is used to lay them flat to ensure that each layer is aligned without offset and the edge overlap error is ≤±1 mm.
[0078] Adjust the equipment parameters: ultrasonic frequency 30 kHz, frequency fluctuation ≤ ±1 kHz, welding pressure 0.2 MPa, welding time 1.0 s, and pressure holding time 2.0 s. Start the ultrasonic welding equipment. The high-frequency vibration causes local melting of the polymer material at the contact surfaces of each layer. The interlayer interface is compacted with the help of the pressure holding device. After the molten area cools and solidifies, the interlayer peel strength is ≥1.5 N / 15 mm, completing the strong composite of the multilayer structure and obtaining the dressing semi-finished product.
[0079] The semi-finished dressing is placed in a punching die, and the punching pressure and stroke are set. The dimensional error of the finished product after punching is ≤ ±0.5 mm. The punching process yields a finished medical dressing of the preset size, such as... Figure 3 As shown in A and B; after sterilization with ethylene oxide, it is vacuum-sealed in an aseptic environment.
[0080] Example 2 (1) Preparation of contact layer S11. Preparation of spinning solution: Weigh 0.8 g of chitosan and 6 g of polycaprolactone, and add them to a 1 wt% acetic acid aqueous solution-ethanol mixed solvent with a volume ratio of 3:2, wherein there are 120 mL of 1 wt% acetic acid aqueous solution and 80 mL of ethanol; under a water bath at 45 ℃, stir magnetically at 400 r / min for 1.2 h until the polymer is completely dissolved; then add 0.85 g of tea tree oil; use ultrasonic dispersion at 250 W and 20 kHz for 15 min; let stand at 25±2 ℃ for degassing for 30 min, and purge with nitrogen gas throughout the process to obtain a uniform and stable spinning solution.
[0081] S12. Electrospinning and Drying: Electrospinning parameters were set as follows: voltage 17 kV, receiving distance 14 cm, feed speed 0.4 mL / h; spinning ambient temperature 18 ℃, relative humidity 40%; the thickness of the collected nanofiber membrane was controlled at 0.15±0.05 mm; after spinning, the fiber membrane was removed and placed in a vacuum drying oven at 30 ℃ and a vacuum degree of -0.08 MPa for 5 h to remove residual solvent, thus obtaining a nanofiber membrane contact layer loaded with natural plant essential oils.
[0082] (2) Preparation of functional layer S21. Preparation of microspheres loaded with anti-inflammatory drugs: Weigh 9g of alginate and 0.8g of compound anti-inflammatory drugs (0.6g of berberine + 0.2g of aloe-emodin), with a mass ratio of anti-inflammatory drugs to microsphere carriers of 0.8:9; add 100mL of deionized water, and after pre-dissolving the anti-inflammatory drugs in a small amount of anhydrous ethanol, add the alginate aqueous solution, and treat with ultrasonic power of 250 W for 17 min in the dark until the system is homogeneous; add the solution dropwise to 1000mL of 2wt% calcium chloride solution at a flow rate of 1.5mL / min, stir at 250 r / min and solidify in the dark for 30 min; filter and collect the microspheres, wash 3 times with deionized water, and dry under vacuum at 35 ℃ and -0.08 MPa for 5 h, with a water content of 8%, to obtain drug-loaded microspheres.
[0083] S22. Preparation of modified starch grafted with polymeric compounds: Weigh 50 g of corn starch and 500 mL of deionized water, and gelatinize at 80℃ for 40 min to obtain starch paste; weigh 10 g of carboxymethyl chitosan, dissolve it in 500 mL of 1 wt% acetic acid solution, dissolve it at 35℃ and add it to the starch paste, and react at 60℃ for 2 h; add 0.8 g of ammonium persulfate and 0.1 g of N,N'-methylenebisacrylamide, and continue to react at 60℃ for 3 h; after the reaction, filter with deionized water 3 times, wash with a gradient of 30 vol% and 50 vol% ethanol, and vacuum dry at 55℃ and -0.08 MPa for 6 h, with a moisture content of 10%, and pulverize through a 100-mesh sieve to obtain carboxymethyl chitosan grafted modified starch.
[0084] S23. Preparation of the functional layer: Weigh 4g of anti-inflammatory drug-loaded microspheres, 4g of modified starch, and 10g of ORC according to a mass ratio of 2:2:5. Mix the three materials and stir evenly. After mixing, add 17 wt% deionized water to adjust to a spreadable paste. Demold with medical-grade silicone oil and spread into a 2 mm thin sheet. Apply pressure of 0.8 MPa. Dry under vacuum conditions at 30 ℃ for 1 h and 50 ℃ for 1 h, with a vacuum degree of -0.08 MPa and a moisture content controlled at 9%. After molding, sterilize with 60 Co γ-rays to obtain the functional layer.
[0085] (3) Preparation of support layer PLA and PCL granules were dried at 50℃ for 3 h and then at 60℃ for 5 h, respectively. They were then mixed at a mass ratio of 7:3, with 2.5 wt% of medical-grade compatibilizer added. The mixture was stirred at 1000 r / min for 15 min in a high-speed mixer. The temperatures in each zone of the meltblown extruder were 175℃, 185℃, and 190℃, with a screw speed of 40 r / min. The fibers were drawn into fibers using a high-temperature airflow at 200℃ and 0.4 MPa, controlling the fiber web weight to 20 g / m². 2Gradient hot air setting at 65 ℃ for 5 min and 85 ℃ for 10 min; sterilization at 45 ℃ and 0.15 MPa with ethylene oxide concentration of 500 mg / L for 2.5 h, followed by ventilation and desorption at 40 ℃ and 50% humidity for 7 days to obtain the support layer.
[0086] (4) Preparation of backing layer PBS raw material was dried at 70 ℃ and -0.08 MPa vacuum for 3 h, with a moisture content of <0.2%; the blown film barrel was heated to 125 ℃ at the front, 140 ℃ at the middle, and 145 ℃ at the die head; the blow-up ratio was stretched from 1.5:1 to 2.5:1, cooled and wound up at 20 ℃ and 5 m / s to obtain the base film; preheated at 65 ℃ for 7 s, stretched 3 times in both longitudinal and transverse directions at 85 ℃ to form a 0.1-1 μm microporous membrane; heat-set at 80 ℃ for 20 s, and plasma treatment parameters were the same as in Example 1; sterilized with ethylene oxide for 3 h, analyzed under the same conditions for 7 days, and wound up and cut to obtain the backing layer.
[0087] (5) Composite preparation of finished dressing The layers are cleaned with 150 W plasma for 5 min; laid flat and positioned in layer order, with an edge error ≤ ±1 mm; ultrasonic welding parameters: frequency 20 kHz, welding pressure 0.1 MPa, welding time 0.5 s, holding time 1 s; the interlayer peel strength after welding is ≥1.5 N / 15 mm; the punching dimension error is ≤ ±0.5 mm; and the layers are sterilized with ethylene oxide and then aseptically vacuum sealed.
[0088] Example 3 (1) Preparation of contact layer S11. Preparation of spinning solution: Weigh 1.5g of chitosan and 10g of polycaprolactone, add them to a mixed solvent of acetic acid aqueous solution and ethanol in the same proportion; stir at 45 ℃ and 400 r / min for 1.2 h to completely dissolve; add 0.5g of myrrh essential oil and a mixed essential oil of honeysuckle and artemisia; the ultrasonic dispersion, degassing and nitrogen protection processes are the same as in Example 1.
[0089] S12. Electrospinning and drying: voltage 19 kV, receiving distance 16 cm, feed speed 0.6 mL / h; ambient temperature 25 ℃, relative humidity 50%; fiber membrane thickness 0.15±0.05 mm; vacuum drying process is the same as in Example 1 to obtain the contact layer.
[0090] (2) Preparation of functional layer S21. Preparation of microspheres loaded with anti-inflammatory drugs: 11g of alginate, 1.2g of compound anti-inflammatory drugs (0.6g of chlorogenic acid + 0.6g of gallic acid); the process steps, ultrasonic dispersion, cross-linking into spheres, and drying conditions are the same as in Example 1, and drug-loaded microspheres are obtained.
[0091] S22. Preparation of modified starch grafted with polymeric compounds: Quaternized chitosan and sodium alginate were compounded in equal amounts as grafting modifiers. The starch gelatinization, grafting reaction, initiation of cross-linking, washing, drying and sieving processes were the same as in Example 1 to obtain composite modified starch.
[0092] S23. Preparation of functional layer: Weigh 6g of drug-loaded microspheres, 4g of modified starch and 10g of ORC according to the mass ratio of 3:2:5. The mixing, paste preparation, molding, pressing, segmented vacuum drying and 60 Co γ-ray sterilization processes are the same as in Example 1 to obtain the functional layer.
[0093] (3) Preparation of support layer PLA and PCL were mixed at a mass ratio of 7:3. The drying, compatibilizer addition, melt-blown extrusion, airflow stretching, web forming and shaping, and ethylene oxide sterilization and analysis processes were the same as in Example 1.
[0094] (4) Preparation of backing layer The raw material drying, blown film, biaxial stretching, microporous molding, heat setting, plasma treatment, sterilization and analysis processes are exactly the same as in Example 1.
[0095] (5) Composite preparation of finished dressing The plasma cleaning and layer positioning and alignment processes remain unchanged; the ultrasonic welding parameters are: frequency 40 kHz, welding pressure 0.3 MPa, welding time 2 s, and holding time 3 s; the forming, punching, sterilization, and aseptic packaging processes are the same as in Example 1.
[0096] Example 4 (1) Preparation of contact layer 1.2g of chitosan and 8.5g of polycaprolactone were dissolved in the same solvent system; 0.7g of eucalyptol rosemary and geranium essential oil mixture was added; electrospinning parameters: voltage 18 kV, receiving distance 15 cm, feed speed 0.5 mL / h, temperature 22 ℃, relative humidity 45%; the remaining preparation and drying processes were the same as in Example 1.
[0097] (2) Preparation of functional layer The anti-inflammatory drug used 1.2g of baicalin as a single raw material; the mass ratio of the functional layer raw materials was 2.5:3:4.5, and 5g of baicalin-loaded microspheres, 6g of modified starch, and 9g of ORC were weighed out respectively; the microsphere carrier was sodium alginate; the modified starch was modified by grafting sodium carboxymethyl cellulose; the microsphere preparation, starch modification, mixing and molding, and drying and sterilization processes were the same as in Example 1.
[0098] (3) Preparation of support layer The mass ratio of PLA to PCL was 7:3. The material drying, blending, melt-blown stretching, hot air setting, and ethylene oxide sterilization were all the same as in Example 1.
[0099] (4) Preparation of backing layer The raw materials, blown film, stretching, plasma treatment, and sterilization parameters of Example 1 were used exactly.
[0100] (5) Composite preparation of finished dressing The ultrasonic welding frequency was 30 kHz, the pressure was 0.2 MPa, the welding time was 1.2 s, and the holding time was 2.0 s; the remaining cleaning, positioning, punching, sterilization and packaging processes were the same as in Example 1.
[0101] Example 5 (1) Preparation of contact layer Chitosan 1.0g and polycaprolactone 7.5g were dissolved in a mixed solvent; 0.72g of tea tree oil and Roman chamomile essential oil mixture were added; electrospinning parameters: voltage 18 kV, receiving distance 15 cm, feed speed 0.5 mL / h, temperature 20 ℃, relative humidity 42%; thus, an essential oil-loaded nanofiber membrane contact layer was obtained.
[0102] (2) Preparation of functional layer The anti-inflammatory drug was a mixture of equal parts curcumin and chlorogenic acid, 1.2g; the raw materials for the functional layer were in a mass ratio of 3:2.5:4.5, and 6g of curcumin + chlorogenic acid loaded microspheres, 5g of modified starch, and 9g of ORC were weighed out respectively; the microsphere carrier was alginic acid; the modified starch adopted a composite grafting system of sodium hyaluronate + pectin + polyvinyl alcohol; the microsphere preparation, grafting modification, molding, drying and sterilization processes were the same as in Example 1.
[0103] (3) Preparation of support layer The mass ratio of PLA to PCL was 7:3. The material drying, blending, melt-blown stretching, hot air setting, and ethylene oxide sterilization were all the same as in Example 1.
[0104] (4) Preparation of backing layer Complete set of process parameters, raw material grades, processing conditions and Example 1.
[0105] (5) Composite preparation of finished dressing Plasma cleaning and activation, precise alignment of layers; ultrasonic welding parameters: frequency 25 kHz, pressure 0.15 MPa, welding time 1.5 s, holding time 2.5 s; interlayer strength, punching accuracy, sterilization and packaging requirements are the same as in Example 1.
[0106] Comparative Example 1: Individual Contact Layer The preparation method is the same as that in Example 1.
[0107] Comparative Example 2 (1) Preparation of contact layer: The preparation method is the same as in Example 1, except that chitosan and polycaprolactone are replaced with polypropylene (PP), and no natural plant essential oils are added; (2) Preparation of functional layer: The preparation method is the same as in Example 1, except that the starch and oxidized regenerated cellulose grafted with polymer compounds are replaced with acrylate water-absorbing resin, and no anti-inflammatory drugs are added. (3) Preparation of support layer: The preparation method is the same as in Example 1, except that polylactic acid and polycaprolactone are replaced with polyester (PET) meltblown fabric; (4) Preparation of backing layer: The preparation method is the same as in Example 1, except that the PBS microporous membrane polyethylene (PE) film is used; (5) The preparation method is the same as in Example 1, and the dressing is prepared.
[0108] Comparative Example 3 The preparation method is the same as in Example 1, except that no natural plant essential oils are added to the contact layer.
[0109] Comparative Example 4 The preparation method is the same as in Example 1, except that no anti-inflammatory drugs are added to the functional layer.
[0110] Comparative Example 5 The preparation method is the same as in Example 1, except that in step (5), medical acrylic adhesive is used instead of ultrasonic welding process to composite each layer.
[0111] Sample Analysis I. Contact Layer Testing 1. The contact layer obtained in Example 1 was functionally tested, and the results are shown in Table 1: Table 1: Results of functional testing of the contact layer
[0112] The plant essential oil-loaded contact layer prepared in Example 1, after multiple tests, showed antibacterial rates of 99% and 98% against Staphylococcus aureus and Escherichia coli, respectively, at 24 h, far exceeding the ≥90% standard. The secretion of TNF-α and IL-6 was reduced by 40% compared to the control group, exceeding the ≥30% threshold requirement, demonstrating significant anti-inflammatory and soothing effects. The cytotoxicity rating was Grade 1, meeting the ≤1 grade biocompatibility safety standard. The 24-h cell adhesion rate and 72-h proliferation rate reached 86% and 120%, respectively, both exceeding the threshold requirements of the medical-grade collagen membrane control, effectively guiding epithelial cell migration and repair. The repair-promoting function of the contact layer meets the application requirements of medical dressing contact layers.
[0113] 2. Safety verification tests were conducted on the contact layer loaded with plant essential oils obtained in Example 1. The results are shown in Table 2: Table 2: Safety test results of the contact layer
[0114] The plant essential oil-loaded contact layer prepared in Example 1, after testing for multiple performance indicators, showed that the total residual amount of acetic acid and ethanol solvent was 410 ppm, below the acceptable threshold of 500 ppm; its tensile strength reached 2.5 MPa and its elongation at break was 60%, both meeting the lower limit requirements of their respective indicators; the in vitro degradation rate of the contact layer was 25% after 2 weeks and 68% after 4 weeks, falling within the acceptable range of 20%~30% after 2 weeks and ≥60% after 4 weeks; in multiple contact tests on rabbit skin, no erythema or edema was observed, and the skin irritation score was 0. This contact layer meets the standards and has the basis for application as a medical dressing contact layer.
[0115] 3. The essential oil loading and sustained-release properties of the contact layer loaded with plant essential oils obtained in Example 1 were tested, and the results are shown in Table 3: Table 3: Results of essential oil loading and sustained-release performance tests in the contact layer
[0116] The essential oil-loaded contact layer prepared in Example 1 was tested for its essential oil loading and sustained-release performance. The actual essential oil loading rate of the contact layer was 0.39 wt%, which is within the acceptable range of 0.35%~0.45 wt% of the total mass of the spinning solution. The cumulative in vitro sustained-release rate of essential oil reached 66% after 72 hours, meeting the threshold requirement of ≥60%. The accuracy of essential oil loading and the controllability of sustained release of the contact layer both met the standards, ensuring the continuous effectiveness of the plant essential oil in medical dressing applications.
[0117] II. Testing of Functional Layers 1. The core functionality of the curcumin-loaded alginate drug-loaded microspheres obtained in Example 1 was tested, and the results are shown in Table 4: Table 4: Results of core functionality testing of curcumin-loaded alginate drug-loaded microspheres
[0118] The curcumin-loaded alginate microspheres prepared in Example 1, after functional testing, showed a curcumin loading of 10 wt% and an encapsulation efficiency as high as 98%. In a simulated wound environment, the in vitro curcumin release rates of the microspheres at 24h, 72h, and 7d were 26%, 55%, and 90%, respectively. The in vitro coagulation time was shortened by 45% compared to the control group, meeting the requirement of ≥40%. Cytotoxicity and hemolysis rate were tested, and the results showed that the cytotoxicity was grade 1 and the hemolysis rate was 3%. These drug-loaded microspheres combine excellent drug loading performance, controllable sustained release effect, and reliable biocompatibility, making them suitable for use as functional layers in medical dressings.
[0119] 2. The stability and degradability of the curcumin-loaded alginate microspheres obtained in Example 1 were tested, and the results are shown in Table 5: Table 5: Stability and Degradability Test Results of Curcumin-Loaded Alginate-Loaded Microspheres
[0120] The curcumin-loaded alginate-based drug-loaded microspheres prepared in Example 1 underwent stability and biodegradability testing. Periodic retesting of particle size, drug loading, and release curves showed that the change rate of each indicator was only 7-9%, meeting the threshold requirement of ≤10%, and the microspheres exhibited no adhesion or breakage. The in vitro degradation rate of the microspheres was 35% after 2 weeks and 65% after 4 weeks, both meeting the qualified standards of ≥30% after 2 weeks and ≥60% after 4 weeks. These drug-loaded microspheres possess good storage stability and biodegradability, meeting the application requirements of functional layers in medical dressings.
[0121] 3. The pure chitosan, pure corn starch, and the obtained modified corn starch from Example 1 were analyzed by Fourier transform infrared spectroscopy (FT-IR). The results are shown in Table 6: Table 6: FT-IR detection results of pure chitosan, pure corn starch, and modified corn starch
[0122] Fourier transform infrared spectroscopy (FT-IR) was used to characterize the chemical structures of pure chitosan, pure corn starch, and chitosan-grafted modified corn starch. The results confirmed that the modified corn starch successfully achieved chitosan grafting and cross-linking.
[0123] Pure chitosan 1600~1650 cm -1 and 3400~3500 cm -1 The characteristic absorption peak of amino groups is observed at 1000–1100 cm⁻¹. -1 The polysaccharide COC stretching vibration peak is present at [value missing]; pure corn starch only shows peaks at 1028–1035 cm⁻¹. -1 A COC stretching vibration peak appears at the position, but no characteristic peaks of amino and ester carbonyl groups are observed.
[0124] Compared to the pure sample, the modified corn starch showed better performance at 1600-1650 cm⁻¹. -1 The presence of an amino characteristic peak at 1700-1750 cm⁻¹ indicates that chitosan has been grafted onto the starch molecular chain; -1 The newly emerging characteristic peak of the ester carbonyl group confirms that the crosslinking agent N,N'-methylenebisacrylamide participated in the crosslinking reaction; its 1000~1100 cm⁻¹ -1 The peak intensity of COC stretching vibration at the point decreased by 20-30%, and the peak center shifted by 5-10 cm. -1 This indicates that the chemical environment of starch molecules changes due to grafting and cross-linking.
[0125] 4. The chitosan-grafted modified starch obtained in Example 1 was subjected to medical safety testing, and the results are shown in Table 7: Table 7: Medical Safety Test Results of Chitosan-Grafted Modified Starch
[0126] The chitosan-grafted modified starch prepared in Example 1, after medical safety and key performance testing, showed a relative cell growth rate (RGR) of 95% and a toxicity rating of Grade 1, meeting the non-toxic requirements of a relative cell growth rate ≥80% and a Grade 1 rating. The skin irritation index was 0.3, with no irritating reactions such as erythema or edema, meeting the safety threshold of an irritation index ≤0.5. The modified starch had a water absorption ratio of 65 g / g and a water retention rate of 85%, both exceeding the qualified standards of ≥50 g / g and ≥80%.
[0127] This chitosan-grafted modified starch possesses both excellent biocompatibility and water absorption and retention properties, making it a high-quality base material for medical dressings.
[0128] 5. The degradation performance of the chitosan-grafted modified starch obtained in Example 1 was tested, and the results are shown in Table 8: Table 8: Test results of the degradation performance of chitosan-grafted modified starch
[0129] The chitosan-grafted modified starch prepared in Example 1 exhibited good degradation performance. After soaking in a PBS buffer environment with pancreatic amylase for 7 days, the in vitro enzymatic degradation rate of the modified starch, measured by the weight loss method, was 35%, meeting the acceptable threshold requirement of ≥30%. This modified starch possesses excellent enzymatic degradation characteristics and is suitable for the biodegradable application requirements of medical dressings.
[0130] 6. The core functionality of the functional layer obtained in Example 1 was tested, and the results are shown in Table 9: Table 9: Results of Core Functionality Testing in the Functional Layer
[0131] The functional layer prepared in Example 1, after testing of multiple core functional indicators, showed a saline absorption rate of 12 mL / (g·min) and a maximum absorption ratio of 38 g / g, both of which meet the requirements for rapid absorption and carrying of large amounts of wound exudate.
[0132] The in vitro coagulation time of this functional layer was shortened by 55% compared with the blank group, and the platelet adhesion rate reached 76%, demonstrating excellent hemostatic performance. The in vitro release rates of curcumin at 24h, 72h, and 7d were 20%, 50%, and 80%, respectively, which met the controlled release standard.
[0133] The anti-inflammatory activity reduced TNF-α and IL-6 secretion levels by 40% compared to the control group, meeting the requirements for anti-inflammatory applications. It exhibited a cytotoxicity rating of Grade 1 and a skin irritation score of 0, with no significant toxic side effects. The in vitro degradation rate reached 53% after 4 weeks, meeting the requirements for biodegradability. This functional layer combines highly efficient exudate management, hemostasis, anti-inflammation, and controlled drug release capabilities with reliable biosafety and biodegradability, making it an ideal choice for a medical dressing functional layer.
[0134] 7. The functional layer security test results for Example 1 are shown in Table 10: Table 10: Functional Layer Security Test Results
[0135] The functional layer prepared in Example 1, after testing for multiple safety indicators, showed the following: residual silicone oil content was 0.08 wt%, below the threshold of ≤0.1 wt%; the finished product moisture content was 7.5 wt%, within the acceptable range of 6 wt%–9 wt%; the total heavy metal content was 8 ppm, meeting the safety requirement of ≤10 ppm; the free aldehyde content was 0.03 wt%, meeting the standard of ≤0.05%; the residual free radicals after 60Co γ-ray sterilization were 0.005 mg / kg, below the limit of ≤0.01 mg / kg; and no microorganisms were detected in the functional layer, meeting the sterility requirements.
[0136] The residual impurities, physicochemical indicators and sterility of this functional layer all meet the standards, and it has reliable medical safety.
[0137] III. Testing of the Support Layer 1. The functional suitability of the support layer meltblown nonwoven fabric obtained in Example 1 was tested, and the results are shown in Table 11: Table 11: Functional Suitability Test Results of the Support Layer Meltblown Nonwoven Fabric
[0138] The medical-grade meltblown nonwoven fabric for the support layer prepared in Example 1 underwent functional suitability testing, and the liquid permeation rate of the support layer was 1.8 mL / cm. 2 h, less than 2 mL / cm 2 The acceptable threshold for h; air permeability is 550 mm / s, which is higher than the acceptable threshold of ≥500 mm / s; moisture permeability is 2200 g / m. 2 • 24h, above ≥2000 g / m 2 • The 24-hour pass threshold is met, and all three core indicators are up to standard, satisfying the performance requirements for the medical dressing support layer.
[0139] 2. The biocompatibility of the support layer meltblown nonwoven fabric obtained in Example 1 was tested, and the results are shown in Table 12: Table 12: Biosafety Test Results of Support Layer Meltblown Nonwoven Fabric
[0140] The support layer meltblown nonwoven fabric prepared in Example 1 underwent biosafety testing. The relative cell proliferation rate of the support layer reached 85%, and the toxicity rating was Grade 1, meeting the requirements of a relative cell proliferation rate ≥70% and a toxicity rating ≤1. The skin irritation reaction score was 0, with no irritation such as erythema or edema. The skin sensitization index was 0.5, meeting the threshold of a sensitization index ≤1 and no delayed-type hypersensitivity reaction. The sterility met the qualified standard for sterility. All four biosafety indicators met the standards, satisfying the biosafety requirements for medical dressings.
[0141] IV. Backing Layer Testing 1. The functional suitability of the PBS microporous membrane backing layer obtained in Example 1 was tested, and the results are shown in Table 13: Table 13: Results of Functional Suitability Tests for Backing Layer PBS Microporous Membrane
[0142] The functional suitability test of the PBS microporous membrane prepared in Example 1 showed that the PBS microporous membrane exhibited no liquid leakage for 30 minutes under a pressure of 0.1 MPa, meeting the threshold requirement for leak-proof performance; the air permeability was 5200 cm³. 3 / (m 2 • 24h • 0.1MPa), higher than ≥5000cm 3 / (m 2 The acceptable threshold for moisture permeability is 0.1 MPa (24h); the permeability reaches 2100 g / (m³). 2 •24h), reaching ≥2000g / (m 2 The acceptable threshold for 24 hours was 8.5%; after immersion in simulated body fluid at 37°C and pH 7.4 for 4 weeks, the mass loss rate was higher than the acceptable threshold of ≥5%.
[0143] All four indicators met the standards, satisfying the performance requirements of the medical dressing backing layer for leak prevention, breathability, moisture permeability, and biodegradability.
[0144] 2. The biosafety of the PBS microporous membrane with backing layer obtained in Example 1 was tested, and the results are shown in Table 14: Table 14: Biosafety Test Results of PBS Microporous Membrane Backing Layer
[0145] The biosafety test of the PBS microporous membrane for the backing layer prepared in Example 1 showed that the relative cell growth rate (RGR) of the PBS microporous membrane was 75% and the toxicity rating was 1, which met the qualified threshold of relative cell growth rate ≥70% and toxicity rating ≤1; the skin irritation reaction score was 0, with no irritation such as erythema or edema; the sterility test result was sterile, which met the sterility requirements; all biosafety indicators met the standards and met the biosafety requirements for the backing layer of medical dressings.
[0146] V. Testing of Medical Dressings 1. The interlayer composite quality of the medical dressing product obtained in Example 1 was tested, and the results are shown in Table 15: Table 15: Results of interlayer bonding quality testing for finished medical dressings
[0147] The interlayer bonding quality of the medical dressing obtained in Example 1 was tested. The interlayer peel strength reached 1.7 ± 0.1 N / 15 mm, meeting the acceptable threshold of ≥ 1.5 N / 15 mm. There were no instances of incomplete or excessive welding in the welded areas, and the weld width was uniform. The dimensional error of the finished product was ± 0.3 mm, meeting the requirement of ≤ ± 0.5 mm. All three test indicators met the standards, indicating that the interlayer bonding quality of the medical dressing meets the technical requirements.
[0148] 2. The functional integration effectiveness of the finished medical dressing obtained in Example 1 was tested, and the results are shown in Table 16: Table 16: Results of Functional Integration Effectiveness Testing of Finished Medical Dressings
[0149] The functional integration effectiveness of the medical dressing obtained in Example 1 was tested. The dressing achieved a comprehensive antibacterial rate of 95% against the two bacteria, meeting the requirement of ≥90% antibacterial rate against Staphylococcus aureus and Escherichia coli. The liquid absorption was 12 times its own weight and the absorption rate was 1.5 min / g, which meets the qualified threshold of ≥10 times absorption and ≤2 min / g absorption rate.
[0150] The external hemostasis time is 4 minutes, lower than the standard of ≤5 minutes; no leakage occurs after 30 minutes under 0.1 MPa pressure, meeting the leakage prevention performance standard; the air permeability is 5200 cm³. 3 / (m 2 • 24h • 0.1MPa), moisture permeability is 2100g / (m²) 2 The levels of the drug (24h) were all above the corresponding minimum limits; the cumulative controlled release rate of the drug over 24 hours was 70%, falling within the acceptable range of 60% to 80%. All indicators met the standards, confirming that the medical dressing possesses excellent functional integration.
[0151] 3. The biosafety of the finished medical dressing obtained in Example 1 was tested, and the results are shown in Table 17: Table 17: Biosafety Test Results of Finished Medical Dressings
[0152] The biosafety test of the medical dressing obtained in Example 1 showed that the relative growth rate (RGR) of the dressing was 80% and the toxicity rating was level 1, which meets the requirements of RGR ≥ 70% and toxicity rating ≤ 1. The irritation score of multiple skin contact tests was 0, with no irritation reactions such as erythema or edema. The sensitization index was 0.5, which meets the qualified threshold of sensitization index ≤ 1 and no delayed-type hypersensitivity reaction. The residual amount of ethylene oxide was 5 μg / g, which is lower than the limit of ≤ 10 μg / g.
[0153] The sterility test result was sterile, achieving a sterility assurance level (SAL) ≤10. -6 The standards were met, and all indicators were satisfied, indicating that the medical dressing has good biocompatibility.
[0154] 4. The degradation performance of the medical dressing product obtained in Example 1 was tested, and the results are shown in Table 18: Table 18: Test Results of Degradation Performance of Finished Medical Dressings
[0155] The medical dressing obtained in Example 1 underwent degradation performance testing. After immersion in simulated body fluid at 37°C and pH 7.4 for 28 days, the mass loss rate was 7.5%, meeting the acceptable threshold of ≥5%. Under the same conditions, the mass loss rate after immersion for 30 days was 8%, also exceeding the standard requirement of ≥5%. Both indicators met the standards, indicating that the medical dressing possesses the required biodegradability.
[0156] 5. Test on wound healing and antibacterial / anti-inflammatory effects The bio-based biodegradable high-efficiency antibacterial medical dressing prepared in Example 1 was compared with the excipients in Comparative Examples 1-5. The concentration levels of inflammatory factors were detected using enzyme-linked immunosorbent assay (ELISA) according to YY / T 0471.5-2017 (bacterial resistance) and YY / T 1465.2-2016 (antibacterial properties). Combined with in vitro cell scratch assays, wound repair and antibacterial / anti-inflammatory functions were compared. The results are as follows: Figure 2 As shown in Table 19.
[0157] Table 19: Results of Antibacterial and Anti-inflammatory Effects Tests for Examples 1 and Comparative Examples 1-5
[0158] As shown in Table 19, the medical dressing of Example 1 showed an antibacterial rate of 94.2±1.5% against Staphylococcus aureus, an anti-inflammatory duration of 76.5±3.2 h, and an epithelial cell crawling rate increase of 55.3±4%. The performance indicators of Comparative Examples 1-5 were significantly lower than those of the Example group, with antibacterial rates ranging from 56.8% to 93.8%, anti-inflammatory durations of only 21.3 to 75.8 h, and the lowest epithelial cell crawling rate increase of only 18.5%. Overall, Example 1 exhibited the best comprehensive performance in antibacterial, anti-inflammatory, and wound repair properties.
[0159] 6. Leakage Management and Air Permeability Testing The bio-based biodegradable high-efficiency antibacterial medical dressing prepared in Example 1 was compared with the excipients of Comparative Examples 1 to 5 in terms of exudate management and air permeability testing according to YY / T 0471.1-2004 / GB / ISO 15496 / pressure osmosis method. The results are shown in Table 20.
[0160] Table 20: Results of seepage management and air permeability tests in Example 1 and Comparative Examples 1-5
[0161] As shown in Table 20, the water absorption rate of the medical dressing in Example 1 was 53.8 ± 2.5 g / g, and the water vapor transmission rate reached 2150 ± 50 g / (m²). 2 •24h), and there is no backflow phenomenon.
[0162] The water absorption rates of Comparative Examples 1 and 3 were close to those of the Example Group, at 52.1±2.3 g / g and 52.5±2.4 g / g, respectively. Their water vapor transmission rates were slightly lower than those of the Example Group. Comparative Example 1 showed slight backflow, while Comparative Example 3 showed no backflow.
[0163] Comparative Example 2 showed a water absorption rate of 38.5 ± 2.1 g / g and a water vapor transmission rate of 1480 ± 45 g / (m²). 2 The levels of 24h and 24h were significantly lower than those of other groups, with only the anti-reflow performance meeting the standard.
[0164] The performance indicators of Comparative Examples 4 and 5 were basically the same as those of the Example Group, with water absorption rates ranging from 52.8±2.3 to 53.1±2.2 g / g and water vapor transmission rates ranging from 2110±49 to 2130±47 g / (m²). 2 (24h), and there was no backflow.
[0165] In summary, the medical dressing of Example 1 exhibits the best overall performance in terms of exudate management and breathability.
[0166] 7. Structural stability and mechanical property testing The bio-based biodegradable high-efficiency antibacterial medical dressing prepared in Example 1 was compared with the excipients of Comparative Examples 1 to 5 in terms of structural stability and mechanical properties, with reference to GB / T 2790-1995 / GB / T 1040.3-2006. The results are shown in Table 21.
[0167] Table 21: Results of structural stability and mechanical properties of Examples 1 and Comparative Examples 1-5
[0168] As shown in Table 21, the interlayer peel strength of the medical dressing in Example 1 is 1.7±0.1 N / 15mm, the tensile strength of the support layer is 2.8±0.2 MPa, and the elongation at break of the support layer is 17.5±1.2%. All mechanical properties are balanced and stable.
[0169] Comparative Example 1 had no interlayer peel strength data, and its tensile strength of the support layer (2.0±0.1 MPa) and elongation at break (9.8±1.0%) were significantly lower than those of the Example Group.
[0170] The interlaminar peel strength (1.2±0.1 N / 15mm) of Comparative Example 2 was lower than that of Example Group, while the tensile strength of the support layer (3.1±0.2 MPa) and the elongation at break (21.5±1.3%) were higher than those of Example Group, indicating an imbalance in mechanical properties.
[0171] The indicators of Comparative Examples 3 and 4 are basically the same as those of the Example Group; the interlayer peel strength (0.8±0.1N / 15mm) of Comparative Example 5 is lower, while the other indicators are close to those of the Example Group.
[0172] In summary, the medical dressing of Example 1 exhibits the best structural stability and mechanical properties, meeting the requirements for dressing structural strength in clinical applications.
[0173] 8. Medical safety and biodegradability The bio-based biodegradable high-efficiency antibacterial medical dressing prepared in Example 1 was compared with the excipients of Comparative Examples 1 to 5 in terms of medical safety and biodegradability, according to ISO 10993-10:2010 / ISO 10993-5:2009 / ISO 10993-13. The results are shown in Table 22.
[0174] Table 22: Medical safety and biodegradability test results of Example 1 and Comparative Examples 1-5
[0175] As shown in Table 22, the cytotoxicity rating of the medical dressings in Example 1 was Grade 1, the skin irritation index was 0.3±0.1, and the biodegradable mass loss rate was 7.5% after 4 weeks.
[0176] Comparative Examples 1 and 3-5 also had a cytotoxicity rating of Grade 1, with skin irritation indices ranging from 0.3±0.1 to 0.4±0.1, and a biodegradable mass loss rate of 6.8% to 8% over 4 weeks. However, the product of Comparative Example 2 had a cytotoxicity rating of Grade 2, with a skin irritation index of 1.8±0.2, and because it was a non-bio-based material, there was no data on its biodegradability.
[0177] Overall, the medical safety indicators of Example 1 are stable and controllable, and its biodegradability performance is balanced, comparable to most comparative product products and superior to the product of Comparative Example 2.
[0178] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A bio-based, biodegradable, highly effective antibacterial medical dressing, characterized in that, It includes a contact layer, a functional layer, a support layer, and a backing layer that are integrated into one piece. The contact layer is a nanofiber membrane loaded with natural plant essential oils, and the functional layer is a composite layer composed of microspheres loaded with anti-inflammatory drugs, modified starch, and oxidized regenerated cellulose. The method for preparing the bio-based, biodegradable, highly effective antibacterial medical dressing includes the following steps: (1) Preparation of contact layer: Chitosan and polycaprolactone are added to a mixed solvent of acetic acid aqueous solution and ethanol, stirred in a water bath until dissolved, and then natural plant essential oil is added. After ultrasonic degassing, a spinning solution is obtained. The spinning solution is electrospun and dried to obtain a contact layer of nanofiber membrane loaded with natural plant essential oil. (2) Preparation of functional layer: anti-inflammatory drugs and microsphere carriers are mixed and cross-linked to obtain microspheres loaded with anti-inflammatory drugs; polymer compounds and starch are subjected to cross-linking reaction to obtain modified starch grafted with polymer compounds; microspheres loaded with anti-inflammatory drugs, modified starch and oxidized regenerated cellulose are mixed, demolded and dried to obtain functional layer; (3) Preparation of support layer: Polylactic acid and polycaprolactone are mixed evenly by melt extrusion, and then drawn into fiber filaments by high temperature airflow. After hot air gradient shaping and sterilization, the support layer of polylactic acid and polycaprolactone composite meltblown nonwoven fabric is obtained. (4) Preparation of backing layer: Polybutylene succinate is melt-extruded and blown to obtain a base film. The base film is biaxially stretched to form a microporous membrane with uniform pore size. After shaping and sterilization, the backing layer of polybutylene succinate microporous membrane is obtained. (5) The plasma-activated contact layer, functional layer, support layer and backing layer are sequentially composited by ultrasonic welding to obtain a bio-based biodegradable high-efficiency antibacterial medical dressing.
2. The bio-based biodegradable high-efficiency antibacterial medical dressing according to claim 1, characterized in that, The nanofiber membrane is composed of chitosan and polycaprolactone, with a mass ratio of chitosan to polycaprolactone of 0.8~1.5:6~10.
3. The bio-based biodegradable high-efficiency antibacterial medical dressing according to claim 1, characterized in that, The natural plant essential oils mentioned are one or more of the following: thyme essential oil, lavender essential oil, tea tree essential oil, Roman chamomile essential oil, eucalyptol-type rosemary essential oil, geranium essential oil, myrrh essential oil, artemisia essential oil, peppermint essential oil, and honeysuckle essential oil; the mass ratio of essential oils to nanofiber membranes is 1:8~25.
4. The bio-based biodegradable high-efficiency antibacterial medical dressing according to claim 1, characterized in that, The anti-inflammatory drugs in the microspheres loaded with anti-inflammatory drugs are one or more of curcumin, berberine, baicalin, aloe-emodin, chlorogenic acid, and gallic acid, and the microsphere carrier is alginate or alginic acid.
5. The bio-based biodegradable high-efficiency antibacterial medical dressing according to claim 4, characterized in that, The mass ratio of the anti-inflammatory drug to the microsphere carrier is 8~12:90~110.
6. The bio-based biodegradable high-efficiency antibacterial medical dressing according to claim 1, characterized in that, The modified starch is modified by grafting with a polymer compound, which is one or more of chitosan, carboxymethyl chitosan, quaternized chitosan, sodium alginate, sodium carboxymethyl cellulose, sodium hyaluronate, pectin, and polyvinyl alcohol.
7. The bio-based biodegradable high-efficiency antibacterial medical dressing according to claim 1, characterized in that, In the functional layer, the mass ratio of microspheres loaded with anti-inflammatory drugs, modified starch, and oxidized regenerated cellulose is 2~4:2~6:4~10.
8. The bio-based biodegradable high-efficiency antibacterial medical dressing according to claim 1, characterized in that, In step (1), the parameters of electrospinning are as follows: voltage is 17~19 kV, receiving distance is 14~16 cm, feed speed is 0.4~0.6 mL / h, temperature is 18~25 ℃, and relative humidity of the environment is 40%~50%.
9. The bio-based biodegradable high-efficiency antibacterial medical dressing according to claim 1, characterized in that, In step (5), the parameters for ultrasonic welding are: ultrasonic frequency 20~40 kHz, welding pressure 0.1~0.3 MPa, welding time 0.5~2 s, and holding time 1~3 s.
Citation Information
Patent Citations
Preparation method for aromatic and bacteriostatic chitosan-based wound dressing
CN104784743A
Preparation method of medical dressing
CN104857553A
Preparation method of medical dressing
CN110433320A
Preparation method for chitosan-based electrostatic spinning combined wound dressing
CN103550816A
Regenerated oxidized cellulose composite hemostatic material and preparation method thereof
CN118892570A